2015
DOI: 10.1021/acs.organomet.5b00686
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to an Oxido-Alkylidene Complex of Mo(VI)

Abstract: The first well-defined Mo oxido-alkylidene complex, [(tBu3PN)2Mo­(O)­(CHSiMe3)] (4), and its borane adduct, [(tBu3PN)2Mo­(O–B­(C6F5)3)­(CHSiMe3)] (5), have been prepared through alkylation of the bis­(phosphinimide) Mo oxido-dichlorido complex [(tBu3PN)2MoOCl2] (3). The reaction between 2 equiv of tBu3PN–SiMe3 (2) and [(DME)­MoO2Cl2] (1) generates 3 through selective elimination of (Me3Si)2O. All complexes have been studied in solution by multinuclear NMR spectroscopy and in the solid state by X-ray crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…The Mo=O bond length in 2 is substantially elongated in comparison to the parent complex 1 , 1.8221(9) versus 1.7198(18) Å . Previously reported molybdenum(VI) oxido borane adducts showed a similar bond elongation . The bonds from all other donor atoms to the metal center are slightly shortened, causing a decreased flexibility around the metal center, thereby most likely preventing isomerization (vide supra).…”
Section: Resultsmentioning
confidence: 99%
“…The Mo=O bond length in 2 is substantially elongated in comparison to the parent complex 1 , 1.8221(9) versus 1.7198(18) Å . Previously reported molybdenum(VI) oxido borane adducts showed a similar bond elongation . The bonds from all other donor atoms to the metal center are slightly shortened, causing a decreased flexibility around the metal center, thereby most likely preventing isomerization (vide supra).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that upon using sterically demanding alkoxido, amido, and other ligands, bimolecular deactivationm ay be prevented but such compounds tend to be lessr eactive in metathesis reactions. [83][84][85][86][87][88] The investigation of Lewis acid-base interaction in olefin metathesis dates back to Osborn's description of ab ridge between catalyst and cocatalyst as described above (section 2), however, B(C 6 F 5 ) 3 was at that time not considered. [29] Significant reactivity enhancemento ft he oxido alkylidene catalysts used in metathesis reactions was achieved by addition of the borane Lewis acid.…”
Section: The Role Of Lewis Acids In Metathesis Reactionsmentioning
confidence: 99%
“…The adduct [Mo{O-B(C 6 F 5 ) 3 }(CHSiMe 3 )(N = PtBu 3 ) 2 ] (50)w as easily accessible by reactiono ft he parent complex with the borane. [87] The molecular structure, determined by single-crystal X-ray diffraction analysis,r eveals as ignificant elongation of the MoÀOb ond in the adduct compared with the one in the parent oxido complex [MoO(CHSiMe 3 )(N = PtBu 3 ) 2 ]( 0.15 longer, Figure 9). However,t he phosphinimido ligandss eem electronically deactivating as the parentc omplex is inactive towards 1-olefins and is ap oorR OMP catalystf or norbornene.…”
Section: The Role Of Lewis Acids In Metathesis Reactionsmentioning
confidence: 99%
See 2 more Smart Citations